MODIFIKASI TEKNIK PEMANENAN DENGAN PERLAKUAN FISIK DALAM UPAYA PENINGKATAN PRODUKTIVITAS GETAH KEMENYAN TOBA (Styrax sumatrana) - Septborn Winner Simamora; Muhdi Muhdi; Ridwanti Batubara (Program studi Kehutanan USU, 2015)
Styrax sumatrana is one of the flagship plant in North Sumatra which has enough potential to be developed. The research was to know frankincense sap productivity Toba (S. sumatrana) with the modification of the physical treatment by being hit and treated with aluminum foil and closed with a combination of both. Making scractch is done by maked cuts in the skin in a vertical line with a length of 2-3 cm with a depth (depending on the thickness of the skin) to the wood. The results showed that treatment with a physical beating and beating and closure combination significantly different physical treatment, closure, while the physical treatment with a combination of beating and beating and closing were not significantly different. The best in productivity of Styrax sumatrana is beating and combination, the value is 437,82 g/tree/year.Keywords: Styrax sumatrana, sap, modified harvesting techniques, physical treatment